Kinetic studies on degradation of Reactive Red 120 dye in immobilized packed bed reactor by Bacillus cohnii RAPT1 - Padmanaban V.C.; Geed S.R.; Achary A.; Singh R.S. (My University, 2025)
The degradation of Reactive Red 120 using Bacillus cohnii RAPT1 immobilized on polyurethane was studied. Initial experiments indicated that the percentage removal of dye in immobilized batch was significantly higher than batch (without immobilization). The optimum process parameters such as effect of dye concentration, time of immobilization on Poly Urethane Foam, initial inoculum size, pH and temperature for removal of dye were investigated and was found as 200 ppm, 36 h, 300*106 colony forming units/ml, 8.0 and 35 °C respectively. Under optimum conditions, 100% removal of dye was obtained within 4 h. The kinetics of biodegradation for the batch with free cells and immobilised packed batch was found to be IInd order with kinetic constant and initial rate of reaction as 0.0408, 0.084 L/(mg day) and 1632, 3360 (mg/L day) respectively. © 2016 Elsevier Ltd